2001
DOI: 10.1021/jf010879h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molecular Weight Fractions Isolated from Roasted Malt on the Enzyme Activities of NADPH−Cytochrome c−Reductase and Glutathione-S-transferase in Caco-2 Cells

Abstract: In the present study, water-soluble nonenzymatic browning products (melanoidins) formed in roasted malt were separated, quantified, and investigated for their effects on detoxifying mechanisms in intestinal Caco-2 cells. The melanoidins were prepared from roasted malt by hot water extraction, and the water-soluble compounds were separated into different molecular weight (MW) fractions by gel filtration chromatography. By monitoring the effluent at 300 nm, seven molecular fractions I-VII were consecutively coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…Melanoidin fractions of different molecular weights prepared from roasted malt by hot water extraction followed by gel filtration chromatography were demonstrated to modulate the CCR and GST activity in human intestinal Caco-2 cells. Again, the LMW fraction of 10 kDa was most effective in enhancing the CCR and the GST activity (+ 122% and + 33% vs. control, respectively) [27].…”
Section: Effect On Mrps and Melanoidins On Xenobiotic Chemopreventivmentioning
confidence: 89%
See 1 more Smart Citation
“…Melanoidin fractions of different molecular weights prepared from roasted malt by hot water extraction followed by gel filtration chromatography were demonstrated to modulate the CCR and GST activity in human intestinal Caco-2 cells. Again, the LMW fraction of 10 kDa was most effective in enhancing the CCR and the GST activity (+ 122% and + 33% vs. control, respectively) [27].…”
Section: Effect On Mrps and Melanoidins On Xenobiotic Chemopreventivmentioning
confidence: 89%
“…Effects on the chemopreventive potential Induction of chemopreventive enzymes in in vitro and in vivo systems by model and food melanoidin mixtures [5,11,26,27] as well as by novel, chemically identified compounds [28,29,30].…”
Section: Intestinal Fate Of Dietary Mrps and Melanoidinsmentioning
confidence: 99%
“…More recent reports, however, have indicated that melanoidins include a LMW fraction, too (Cosovic et al, 2010;Faist, Lindenmeier, Geisler, Erbersdobler, & Hofmann, 2002;Glosl et al, 2004). In real foods, most of the melanoidins have been shown to be HMW compounds.…”
Section: Molecular Weight Of Melanoidinsmentioning
confidence: 99%
“…It is known that MRPs contain high concentrations of Ne-carboxymethyllysine (CML), a compound known to induce CCR and inhibit GST Faist, Lindenmeier et al, 2002), which may partially explain the effects of melanoidin fractions on CCR and GST . However, this xenobiotic enzyme-modulating activity cannot be entirely explained by the presence of CML, as it seems various reaction products formed during the heat-treatment of food and model systems, such as MRPs and native polyphenols, also contribute to this effect, which could help to explain the discrepancies in the above investigations.…”
Section: Effect Of Melanoidins On Xenobiotic Enzymes Activitymentioning
confidence: 99%
“…Total cellular membranes were prepared by differential centrifugation as described (García et al, 2001) and resuspended in 100 μl of 0.3 M sucrose (with protease inhibitors). In order to evaluate GST protein content and activity, cytosolic fractions from Caco-2 cells were obtained by ultracentrifugation as described previously (Faist et al, 2002).…”
Section: Methodsmentioning
confidence: 99%